The Influence of Management and Silvicultural Practices on The Incidence of Heart Rot in Acacia Mangium Plantations - Md. Noor, Hashim (1993)
Acacia mangium Willd., a major exotic timber species used in the Compensatory Forest Plantation Program for the product ion of saw logs, was found to be infected by heart rot. To evaluate the incidence and severity of heart rot in A. mangium plantations, a study consisted of laboratory investigations and field surveys was conducted. The laboratory studies include isolation of fungi from infected tree, determination of wood density, microscopic observations, and chemical wood analyses. Field surveys were conducted at five plantations, namely Rantau Panjang Forest Reserve (RPFR), Bukit Tarek Forest Reserve (BTFR), Kemasul Forest Reserve (KFR), Setul Forest Reserve (SFR), and Ulu Sedili Forest Reserve (USFR).